2011
DOI: 10.1590/s1517-83822011000200037
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of subtilase cytotoxin and relation with other virulence factors in verocytotoxigenic Escherichia coli isolated from food and cattle in Argentina

Abstract: We investigated the presence of the gene of subtilase cytotoxin (SubAB), described in certain highly virulent verocytotoxigenic E. coli strains, in isolates from Argentina and its relation with other virulence factors. The gene subA was present in eae-negative strains mostly associated with saa, vt2 and ehxA genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Such carriage rate was strikingly similar to the other comprehensive research which found this gene in 25% of bovine and 91.9% of sheep and goats STEC in Spain [12]. In Brazil, 21 out of 95 STEC collection strains (22%) were positive in subA PCR which mainly targets the subAB1 [31]. Such surprising similarity in carriage of subAB may re ect the very old macroevolutionary events in LEE-negative lineages which occurred in E. coli population within different hosts regardless of the geographical region.…”
Section: Discussionsupporting
confidence: 88%
“…Such carriage rate was strikingly similar to the other comprehensive research which found this gene in 25% of bovine and 91.9% of sheep and goats STEC in Spain [12]. In Brazil, 21 out of 95 STEC collection strains (22%) were positive in subA PCR which mainly targets the subAB1 [31]. Such surprising similarity in carriage of subAB may re ect the very old macroevolutionary events in LEE-negative lineages which occurred in E. coli population within different hosts regardless of the geographical region.…”
Section: Discussionsupporting
confidence: 88%
“…SubAB intraperitoneal injection in mice led to striking resemblances with STEC-associated HUS in humans, as well as to leukocytosis, thrombocytopenia, and renal cell and liver damage [91]. The contribution of SubAB to human HUS pathophysiology is currently unclear but is thought to act in synergy with Shiga toxins to enhance clinical manifestations of STEC infections [92,93].…”
Section: Subtilase Cytotoxinmentioning
confidence: 99%
“…This BiP cleavage by SubAB triggers the ER stress response mediated by protein kinase R-like ER kinase (PERK), inositol-requiring kinase 1α (IRE1α), and activating transcription factor 6 (ATF6) ( Wolfson et al., 2008 ), which leads to cell death ( May et al., 2010 ; Paton et al., 2006 ; Wolfson et al., 2008 ; Yahiro et al., 2010 , 2012 ) and damage in mice including hemorrhagic colitis ( Furukawa et al., 2011 ; Wang et al., 2007 , 2011 ). The subAB gene was detected in some LEE-negative STEC strains including clinical human isolates ( Fierz et al., 2017 ; Hoang Minh et al., 2015 ; Khaitan et al., 2007 ; Paton et al., 2004 ), which suggests that SubAB may exacerbate clinical symptoms of STEC infections ( Galli et al., 2010 ; Velandia et al., 2011 ). However, the role of SubAB in STEC infections remains unclear.…”
Section: Introductionmentioning
confidence: 99%